Circulating CTRP9 correlates with the prevention of aortic calcification in renal allograft recipients. - Nobuhiko Miyatake; Hiroki Adachi; Kanae Nomura-Nakayama; Keiichiro Okada; Kazuaki Okino; Norifumi Hayashi; Keiji Fujimoto; Kengo Furuichi; Hitoshi Yokoyama (PLoS ONE, 2020)
Background Cardiovascular disease (CVD) due to atherosclerosis is a major cause of death in renal allograft recipients. Recently, C1q/TNF-α related protein-9 (CTRP9), which is a paralog of adiponectin (ADPN), has been suggested to be related to the prevention of atherosclerosis and the occurrence of CVD, but this relationship has not been confirmed in renal allograft recipients. Subjects and methods The relationships among the serum CTRP9 concentration, serum ADPN concentration, and vascular calcification were investigated in 50 kidney transplantation recipients at our hospital. Calcification of the abdominal aorta was evaluated according to the aortic calcification area index (ACAI) calculated from CT images. Changes in the serum CTRP9 and ADPN fractions and ACAI were examined for 8 years. In addition, the expression of CTRP9 and ADPN and their respective receptors AdipoR1 and R2 in muscular arteries of the kidney was examined by immunofluorescence. Results In renal allograft recipients, the serum CTRP9 concentration at the start of the observation was not significant correlated with eGFR or serum high-molecular-weight (HMW)-ADPN concentration (rS = -0.009, p = 0.950; rS = -0.226, p = 0.114, respectively). However, the change in the serum CTRP9 concentration was positively correlated with the change in the serum HMW-ADPN concentration (rS = 0.315, p = 0.026) and negatively correlated with the change in ACAI (rS = -0.367, p = 0.009). Multiple regression analysis revealed that the serum HMW-ADPN concentration was a significant positive factor for the change in the serum CTRP9 concentration. Moreover, for ACAI, an increase in the serum CTRP9 concentration was an improving factor, but aging was an exacerbating factor. Furthermore, colocalization of CTRP9 and AdipoR1 was noted in the luminal side of intra-renal arterial intima. Conclusion In renal allograft recipients, both CTRP9 and HMW-ADPN were suggested to prevent the progression of aortic calcification through AdipoR1.